Effect of static mixer on fiber orientation of injection molded fiber‐reinforced composites. (3rd November 2022) - Shotwell, Demitri; Román, Allen Jonathan; Yang, Huaguang; Lin, Chung‐Yin; Glas, Stefanie; Chen, Edward; Osswald, Tim A.; Turng, Lih‐Sheng
Abstract: The effect of an in‐mold static mixer on orientation of fiber‐reinforced polypropylene (PP) was explored within the injection molding process. Several mold geometries and helical mixer designs were assessed via simulation to identify the mixing ability and the potential effect on fiber orientation. It was found that the static mixers within the runner segment could successfully mix the polymer and randomize the fibers but that the fiber alignment reduction was quickly recovered. Injection molding experiments were carried out to verify these simulations using one geometry case. Fiber orientation at different mold locations were measured using micro‐CT (μCT) scans and the degree of fiber orientation was quantified by "goodness of fit" to a normal Gaussian function approach. The experimental fiber orientation results showed good agreement with the simulations. These experiments indicated that the use of a static mixer within the runner system of a mold could be used for mixing the polymer melt after the plasticizing unit of the injection molding machine. However, its effect on changing the overall alignment of the fibers within injection molded parts could be offset by the melt flow downstream of the static mixer, suggesting the importance of mixer location with respect to the part cavity. Abstract : Simulation and experiments were completed to explore the novel mold modification of adding a helical static mixer to the runner system to disrupt fiber alignment in fiber‐reinforced thermoplastic injection molded parts.